The Onfp class in the Magellanic Clouds - Walborn, Nolan Revere (2010)
The Onfp class of rotationally broadened, hot spectra was defined some time ago in the Galaxy, where its membership to date numbers only eight. The principal defining characteristic is a broad, centrally reversed He II λ 4686 emission profile; other emission and absorption lines are also rotationally broadened. Recent surveys in the Magellanic Clouds (MCs) have brought the class membership there, including some related spectra, to 28. We present a survey of the spectral morphology and rotational velocities, as a first step toward elucidating the nature of this class. Evolved, rapidly rotating hot stars are not expected theoretically, because the stellar winds should brake the rotation. Luminosity classification of these spectra is not possible, because the principal criterion (He II λ4686) is peculiar; however, the MCs provide reliable absolute magnitudes, which show that they span the entire range from dwarfs to supergiants. The Onfp line-broadening distribution is distinct and shifted toward larger values from those of normal O dwarfs and supergiants with >99.99% confidence. All cases with multiple observations show line-profile variations, which even remove some objects from the class temporarily. Some of them are spectroscopic binaries; it is possible that the peculiar profiles may have multiple causes among different objects. The origin and future of these stars are intriguing; for instance, they could be stellar mergers and/or gamma-ray-burst progenitors.